Structure of Si nano-clusters in ZnO matrix - R. García (Superficies y vacío, 1999)
The composite films of Si/ZnO were grown on cuartz substrates by co sputtering of Si and ZnO targets. Transmission electron microscope (TEM) images demonstrated a homogeneous distribution of clusters in the matrix with average size varied from 3.7 nm to 34 nm depending on the temperature of annealing. IR absorption measurements revealed the bands correspond to the modes of vibrations of Si3 in its triangular geometrical structure, SiOX and ZnO. By analysing the IR absorption and XPS spectra we could found that the nano-clusters consist of a Si3 core and a SiOX cap layer. With the increase of annealing temperature, the vibrational states of Si changed from the triplet 3B1 (C2n) and 3A 2(D3h ) states to its singlet ground state 1A1 (C2n) and the oxidation state of Si in SiOX increased. The evolution of the IR bands with the variation of Si content in the films and with the variation of the temperature of annealing are discussed